2016
DOI: 10.1080/15592324.2016.1273304
|View full text |Cite
|
Sign up to set email alerts
|

Are avoidance and acclimation responses during hypoxic stress modulated by distinct cell-specific mechanisms?

Abstract: Plants respond to hypoxic stress through either acclimation to the stress or avoidance of it, as they do to most environmental stresses. The hypothesis that has general consensus among the community is that ethylene response factors (ERFs) are central elements that control both types of responses to hypoxia. Recent studies suggest that this may not be the case for all cells experiencing hypoxic stress. Mature maize root cells undergoing hypoxic stress were found to undergo acclimation and avoidance mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Oxidative stress response and redox signalling, including production of ROS and NO as well as other reactive nitrogen species (RNS), is associated with low oxygen stress 45,46 . Production of ROS signalling is associated with the enhanced activity of PM bound NADPH oxidases (RBOH gene), through Ca +2 signalling and phosphorylation, in response to stress perception 47,48 .…”
Section: Hypoxia-induced Ros Production Redox Associated Gene Expresmentioning
confidence: 99%
“…Oxidative stress response and redox signalling, including production of ROS and NO as well as other reactive nitrogen species (RNS), is associated with low oxygen stress 45,46 . Production of ROS signalling is associated with the enhanced activity of PM bound NADPH oxidases (RBOH gene), through Ca +2 signalling and phosphorylation, in response to stress perception 47,48 .…”
Section: Hypoxia-induced Ros Production Redox Associated Gene Expresmentioning
confidence: 99%
“…Shin et al () and Behera et al () have previously shown that low K + conditions led to the generation of ROS. It was also shown that the level of ROS is balanced by Pgbs (Mira et al, ). At the beginning of our analysis, we speculated that the plant's tolerance to low K + might also be due to quenching action of the Pgbs.…”
Section: Discussionmentioning
confidence: 99%
“…Plant Pgbs are known to be differentially expressed under various stresses, such as, hypoxia, nutrient deprivation, osmotic, cold, oxidative, and nitro‐sative stress (Arredondo‐Peter, Moran & Sarath, ; Mira et al, ; Mira, El‐Khateeb, Sayed Ahmed, Hill, & Stasolla, ). The recent reverse genetic approaches on Pgbs in Arabidopsis thaliana have emphasized their paramount role during plant growth and development by demonstrating that at least one functional Pgb gene is necessary for survival of young seedlings (Hebelstrup, Shah, & Igamberdiev, ; Hill, ).…”
Section: Introductionmentioning
confidence: 99%
“…Retention of meristem function and protection of meristematic cells from death under suboptimal environmental conditions have been postulated to be an avoidance strategy modulated by phytoglobins (Pgbs) ( Mira et al , 2017 ). Phytoglobins, formerly known as non-symbiotic plant hemoglobins ( Hill et al , 2016 ), are heme-containing proteins that act as scavengers of nitric oxide (NO) and suppressors of the death program ( Huang et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%